An Analysis of Values in Children's Picture Books in Turkish for 5-6 Year-old Children - Kazancı Gül, Mine; Atay, Mesude (Edp ​​Sciences, 2018)
This study aims to examine the values of wisdom, tolerance, benevolence, happiness, courtesy, respect, love and responsibility in the children's books published in the years between 2000 and 2007 and in 2014 written in Turkish for 5-6 year old children. It is designed in content analysis pattern of qualitative research. A descriptive model of quantitative research methods was used to determine the frequency of values in picture books. The sample of the study consists of 40 children's picture books which are translated into Turkish and written in Turkish for the 5-6 age group determined by the criterion sampling strategy. The researcher developed a checklist as a data collection tool which is values checklist. As a result of the research, there are 46.80% values in the children's picture books published between 2000 and 2007; 53.20% values published in 2014, in analyzed picture books. It is found that children's picture books, those translated into Turkish and those written in Turkish differ in terms of inclusion of values. Regarding results of the study, it is necessary to give more importance to the value of wisdom and tolerance in the children's picture books and to transfer the values through positive examples toward proper behavior.
Keywords: Pre-school Education; Children's Picture Books; Values; Values Education; Children's Literature